Tendon injuries of the knee - Liddle,AD; Rodríguez-Merchán,EC (2016)
Tendon injuries are common in the knee. The most commonly affected structure is the extensor mechanism. The main pathologies are tendonitis of the patella and ruptures of the patellar and quadriceps tendons, although other tendonopathies have rarely been described around the knee. Patellar tendinopathy can be difficult to treat, but the mainstay of treatment is physiotherapy, with injectable and surgical treatment reserved for recalcitrant cases. The diagnosis of quadriceps and patellar tendon ruptures requires a high index of suspicion and thorough history-taking to assess for medical comorbidities that may predispose patients to tendon degeneration. Radiographic assessment with plain films supplemented by ultrasonography (US) and magnetic resonance imaging (MRI) when the diagnosis is equivocal further aids diagnosis, however, advanced imaging is often unnecessary in patients with functional extensor mechanism defi- cits. Acute repair is preferred, and transpatellar bone tunnels serve as the primary form of fixation when the tendon rupture occurs at the patellar insertion, with or without augmentation depending on surgeon preference. Chronic tears are special cases requiring reconstructions with allograft, synthetic grafts or autograft. Rehabilitation protocols generally allow immediate weight-bearing with the knee locked in extension and crutch support. Limited arc motion is started early with active flexion and passive extension and then advanced progressively, followed by full active range of motion and strengthening. Complications are few but include quadriceps atrophy, heterotopic ossification, infection, stiffness and rerupture. Outcomes are excellent if repair is done acutely, with poorer outcomes associated with delayed repair.